Development of Tools for Genetic Analysis of Phenanthrene Degradation and Nanopod Production by Delftia sp. Cs1-4 - Hickey, William J. (Frontiers in Microbiology, 2011)
The bacterium Delftia sp. Cs1-4 produces novel extracellular structures (nanopods) in conjunction with its growth on phenanthrene. While a full genome sequence is available for Strain Cs1-4, genetic tools that could be applied to study phenanthrene degradation/nanopod production have not been reported. Thus, the objectives of this study were to establish such tools, and apply them for molecular analysis of nanopod formation and/or phenanthrene degradation. Three types of tools were developed and/or validated. First, we developed a new expression system based on a strong promoter controlling expression of a surface layer protein (NpdA) from Delftia sp. Cs1-4, which was ca. 2,500-fold stronger than the widely used lactose promoter. Second, the Cre-loxP system was validated for generation of markerless, in-frame, gene deletions, and for in-frame gene insertions. The gene deletion function was applied to examine potential roles in nanopod formation of three genes (omp32, lasI, and hcp), while the gene insertion function was used for reporter gene tagging of npdA. Lastly, pMiniHimar was modified to enhance gene recovery and mutant analysis in genome-wide transposon mutagenesis. Application of the latter to strain Cs1-4, several new genes with potential roles in phenanthrene degradation or npdA expression were identified. Collectively, the availability of these tools has opened new avenues of investigation in Delftia sp. Cs1-4 and other related genera/species with importance in environmental toxicology.